Evaluating carbon dioxide lasers. (1st June 2022) - Ghanem, Ali
Abstract : Mr Ali Ghanem reviews the carbon dioxide lasers that are capable of reversing cutaneous photodamage, fine lines, wrinkles and hyperpigmentation